A Randomized Noninferiority Trial of Intravenous Iron Isomaltoside versus Oral Iron Sulfate in Patients with Nonmyeloid Malignancies and Anemia Receiving Chemotherapy: The PROFOUND Trial. Issue 4 (1st April 2016) - Birgegård, Gunnar; Henry, David; Glaspy, John; Chopra, Rakesh; Thomsen, Lars L.; Auerbach, Michael
Abstract : Study Objective: A safe alternative to erythropoiesis‐stimulating agents to treat anemia is warranted in patients with cancer and anemia; thus the objective of this trial was to compare the efficacy and safety of intravenous (IV) iron isomaltoside with oral iron in patients with cancer and anemia by testing the noninferiority of IV versus oral iron. Design: Phase III, prospective, open‐label, comparative, randomized, noninferiority, multicenter trial. Setting: Forty‐seven hospitals or private cancer clinics in Asia, the United States, and Europe. Patients: A total of 350 patients with cancer and anemia. Intervention: Patients were randomized in a 2:1 ratio to either intravenous iron isomaltoside or oral iron sulfate. Patients in the iron isomaltoside group were then randomized into an infusion subgroup (single intravenous infusions of a maximum dose of 1000 mg over 15 min) or a bolus injection subgroup (bolus injections of 500 mg over 2 min). Measurements and Main Results: The primary efficacy outcome was change in hemoglobin concentration from baseline to week 4. Changes in other relevant hematology variables, effect on quality of life, and safety outcomes were also assessed. The primary efficacy outcome was tested for noninferiority, whereas the remaining outcomes were tested for superiority. Iron isomaltoside was noninferior to oral iron in change in hemoglobin concentration from baseline to week 4 (difference estimate 0.016, 95% confidence interval –0.26 to 0.29, p<0.001). A faster onset of the hemoglobin response was observed with infusion of iron isomaltoside (superiority test: p=0.03 at week 1), and a sustained effect on hemoglobin level was shown in both the iron isomaltoside and oral iron treatment groups until week 24. A significant mean decrease in fatigue score was observed from baseline to week 12 in the iron isomaltoside group (p<0.001) but not in the oral iron group (p=0.057). A higher proportion of patients treated with oral iron experienced adverse drug reactions (18.8% vs 6.6%, p<0.001) and discontinued the trial due to intolerance (8.0% vs 0.9%, p=0.001). Transient hypophosphatemia (phosphate level less than 2 mg/dl) was reported at similar low frequencies among the groups: 7.1% in the iron isomaltoside infusion subgroup versus 8.5% in the iron isomaltoside bolus injection subgroup versus 5.4% in the oral iron group. Conclusion: This trial demonstrated comparable sustained increases in hemoglobin concentration over time with both iron isomaltoside and oral iron. Iron isomaltoside was better tolerated than oral iron, and fatigue was significantly decreased with iron isomaltoside. Low rates of clinically insignificant hypophosphatemia were reported in patients receiving both treatments.